Cytogenetic features of intergeneric amphydiploids and genome-substituted forms of wheat - E. D. Badaeva; R. O. Davoyan; N. A. Tereshchenko; E. V. Lyalina; S. A. S.A. Zoshchuk; N. P. Goncharov (Вавиловский журнал генетики и селекции)
Synthetic intergeneric amphydiploids and genome-substituted wheat forms are an important source for transferring agronomically valuable genes from wild species into the common wheat (Triticum aestivum L.) genome. They can be used both in academic research and for breeding purposes as an original material for developing wheatalien addition and substitution lines followed by translocation induction with the aid of irradiation or nonhomologous chromosome pairing. The chromosome sets and genome constitutions of allopolyploids are usually verified in early hybrid generations, whereas the subsequent fate of these hybrids remains unknown in most cases. Here we analyze karyotypes of five hexa- (2n = 6x = 42) and octoploid (2n = 8x = 56) amphydiploids of wheat with several species of the Aegilops, Haynaldia, and Hordeum genera, and six genome-substituted wheat–Aegilops forms, which were developed over 40 years ago and have been maintained in different gene banks. The analyses involve C-banding and fluorescence in situ hybridization (FISH) with pAs1 and pSc119.2 probes. We have found that most accessions are cytologically stable except for Avrodes (genome BBAASS, a hexaploid genome-substituted hybrid of wheat and Aegilops speltoides), which segregated with respect to chromosome composition after numerous reproductions. Chromosome analysis has not confirmed the presence of the N genome from Ae. uniaristata Vis. in the genome-substituted hybrid Avrotata. Instead, Avrotata carries the D genome. Our study shows that octoploid hybrids, namely AD 7, AD 7147 undergo more complex genome reorganizations as compared to hexaploids: the chromosome number of two presumably octoploid wheatAegilops hybrids were reduced to the hexaploid level. Genomes of both forms lost seven chromosome pairs, which represented seven homoeologous groups and derived from different parental subgenomes. Thus, each of the resulting hexaploids carries a synthetic/hybrid genome consisting of a unique combination of chromosomes belonging to different parental subgenomes.